Success of Immunopathogenetic Therapy for Management of Congenital Ichthyosis, Combined Form, in a Child: Rare Clinical Case - Karine O. Avetisyan; Nikolay N. Murashkin; Ekaterina S. Pavlova; Roman A. Ivanov; Svetlana V. Petrichuk; Daria G. Kuptsova; Dmitrii S. Demyanov; Kirill V. Savostyanov (Вопросы современной педиатрии, 2024)
Background. Congenital ichthyosis (CI) is relating to the group of clinical and genetically heterogeneous severe genodermatoses. SAM syndrome is included in classification of CI syndromic forms. Defects in the desmoplakin (DSP) and desmoglein 1 (DSG1) genes are the prime cause of disease. Impaired function of encoded proteins leads to desmosomal anomalies and disease symptoms. Comorbid atopic syndrome becomes the major cause of diagnostic mistakes. Patients are observed continuously with diagnosis “Atopic dermatitis (AD) torpid to standard treatment methods”. Clinical case description. This article describes a rare case of a boy with severe AD. Despite the chronic dermatosis several systemic disorders were revealed during examination: short stature, protein-energy malnutrition, adrenal insufficiency, juvenile polyarthritis, vitamin D deficiency, onychodystrophy, dysmorphic disorders. Molecular genetic study conducted via high-throughput sequencing followed by validation with Sanger sequencing has revealed two genetic variants: novel variant chr18:28934543G>T in the DSG1 gene in the heterozygous state and pathogenic variant chr5:157468728C>A in the NIPAL4 gene in the homozygous state. As a result, the final diagnosis was established: “SAM syndrome. Congenital ichthyosiform erythroderma”. Flow cytometry immunology study has shown dominant immunological profile of Th17-, and Thact-lymphocyte proliferation. The immunobiological therapy with IL-17A inhibitor, secukinumab, was initiated. Clinical efficacy was evaluated via ISS (Ichthyosis Severity Index), CDLQI (Children’s Dermatology Life Quality Index), pruritus numerical rating scale. ISS was 5.8 points, pruritus scale — 9, CDLQI — 24 at therapy initiation. Improvement in the skin condition was observed after a month of therapy. ISS was 1.2 points, pruritus scale — 2, CDLQI — 4 6 months after the therapy initiation. Conclusion. The diagnosis of a child with combined form of CI made it possible to change the management strategy, to prescribe pathogenetically justified targeted immunobiological therapy, and to achieve significant improvement in the child's health and quality of life, which does not differ from healthy peers.